2016
DOI: 10.1038/srep18576
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for detection of a Type II sex pheromone in the winter moth Operophtera brumata

Abstract: How signal diversity evolves under stabilizing selection in a pheromone-based mate recognition system is a conundrum. Female moths produce two major types of sex pheromones, i.e., long-chain acetates, alcohols and aldehydes (Type I) and polyenic hydrocarbons and epoxides (Type II), along different biosynthetic pathways. Little is known on how male pheromone receptor (PR) genes evolved to perceive the different pheromones. We report the identification of the first PR tuned to Type II pheromones, namely ObruOR1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 61 publications
6
43
0
Order By: Relevance
“…cunea . Differentiation of sex pheromones in various moth species has occurred over many millennia, using diverse biosynthetic pathways involving different enzymes, substrates, and binding sites, resulting in the two major recognized pheromone types [ 29 ]. To date, little is known about the olfactory proteins repertoire species using Type-II pheromones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cunea . Differentiation of sex pheromones in various moth species has occurred over many millennia, using diverse biosynthetic pathways involving different enzymes, substrates, and binding sites, resulting in the two major recognized pheromone types [ 29 ]. To date, little is known about the olfactory proteins repertoire species using Type-II pheromones.…”
Section: Introductionmentioning
confidence: 99%
“…To date, little is known about the olfactory proteins repertoire species using Type-II pheromones. Did they evolve a novel receptors to perceive the Type-II sex pheromones, or were existing pheromone receptors were recruited for detection of the new ligands [ 29 ]? We assume that specific H .…”
Section: Introductionmentioning
confidence: 99%
“…4). One was the so-called PR clade that, as previously observed, contained all type I PRs characterized so far (except SlitOR5) as well as two type II PRs (Zhang et al, 2016). The other three lineages harboring PRs consisted of one containing SlitOR5, one containing EgriOR31 (a type II PR from the geometrid Ectropis grisescens; Li et al, 2017) and one containing EsemOR3 and 5 (type 0 PRs from the non-dytrisian moth Eriocrania semipurpurella; Yuvaraj et al, 2017).…”
Section: A Novel Lineage Of Candidate Moth Pheromone Receptorsmentioning
confidence: 56%
“…Artificial release of lacewings is a well‐known method for suppressing aphids (Zhang et al ., ), but it is difficult to establish populations in the field. Understanding the molecular recognition mechanisms of CpalOBPs and the behavioural responses of C. pallens to plant volatiles and the aphid alarm pheromone has important implications for population establishment after release.…”
Section: Discussionmentioning
confidence: 99%
“…It is found in many different agro‐ecosystems including tea gardens, maize, cotton and rice (Brooks, ; Bai et al ., ). Artificial lacewing release is a well‐known method for suppressing aphids (Zhang et al ., ), but it is difficult to establish lacewing populations in the field. Previous studies have reported that plant‐derived compounds, pest‐induced volatiles and aphid alarm pheromones are used by predators and parasitoids as foraging cues (Al Abassi et al ., ; Xu et al ., ).…”
Section: Introductionmentioning
confidence: 99%